2008
DOI: 10.1152/ajpcell.00315.2007
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation-dependent changes in the membrane properties of fiber cells isolated from the rat lens

Abstract: Impedance measurements in whole lenses showed that lens fiber cells possess different permeability properties to the epithelial cells from which they differentiate. To confirm these observations at the cellular level, we analyzed the membrane properties of fiber cells isolated in the presence of the nonselective cation channel inhibitor Gd3+. Isolated fiber cells were viable in physiological [Ca2+] and exhibited a range of lengths that reflected their stage of differentiation. Analysis of a large population of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 43 publications
3
17
0
Order By: Relevance
“…The increase in the core [Na + ] i must therefore be accompanied by a decrease in [K + ] i . The values of [K + ] i were not measured, but since the value is typically around 145 mM, a 10-mM decrease would have little effect, particularly since the K + conductance is predominantly in the epithelium (Webb and Donaldson 2008), where the GPX-1 KO and WT lenses had the same values of [Na + ] i and [K + ] i . This assumption is supported by the resting voltage data, which show no significant difference between WT and GPX-1 KO lenses.…”
Section: Resultsmentioning
confidence: 99%
“…The increase in the core [Na + ] i must therefore be accompanied by a decrease in [K + ] i . The values of [K + ] i were not measured, but since the value is typically around 145 mM, a 10-mM decrease would have little effect, particularly since the K + conductance is predominantly in the epithelium (Webb and Donaldson 2008), where the GPX-1 KO and WT lenses had the same values of [Na + ] i and [K + ] i . This assumption is supported by the resting voltage data, which show no significant difference between WT and GPX-1 KO lenses.…”
Section: Resultsmentioning
confidence: 99%
“…There are no reports suggesting anterior to equator variations in the expression of epithelial K + channels; however; the anatomical variation from flat cells at the anterior pole to elongated cells at the equator, and the expression of K + channels in new equatorial fibers (208), imply the K + efflux per unit area of lens surface will be highest at the equator, where K + influx via Na + -K + pumps is also highest. Extensive patch-clamp studies conducted mostly in the laboratory of Dr. James Rae (reviewed in Refs.…”
Section: The Mature Lensmentioning
confidence: 99%
“…The problem was twofold: 1 ) fiber cells are not self-sustaining and require gap junction coupling with transporters located in the lens epithelium for homeostasis, and 2 ) the isolation procedure produced a Ca 2+ leak that caused disintegrative vesiculation of the cells. Recently, Webb and Donaldson (208) developed an isolation procedure that allowed fiber cells to remain stable long enough for whole cell patch-clamp analysis. The critical innovation was to treat the cells with Gd 3+ , a blocker of cation channels that were apparently activated by the isolation procedure and mediated the Ca 2+ leak.…”
Section: The Mature Lensmentioning
confidence: 99%
“…9 Although the molecular identity of the Cl Ϫ channels that mediate the circulating Cl Ϫ fluxes remains unclear, patch clamp experiments on isolated fiber cells have allowed the functional properties of the channel(s) that mediate Cl Ϫ fluxes to be characterized. 18,19 By relating fiber cell length to fiber cell position (cell layers) within lens sections, Webb et al 18 showed that isolated fiber cells longer than 120 m originate from the zone of ion influx. Fiber cells of this length exhibited a constitutively active outwardly rectifying Cl Ϫ conductance that exhibited a lyotropic anion selectivity sequence (I Ϫ Ͼ Cl Ϫ ), reminiscent of volume-sensitive Cl Ϫ conductances seen in many cell types.…”
mentioning
confidence: 99%